The relationship between cultural intelligence, emotional intelligence, social intelligence, islamic work ethics and work performance among public service employees in Malaysia - Hartini, Husin (2018)
A high performance public service is increasingly recognised as one of the critical elements in international competitiveness. The success of public service organisations depends on the availability of a globally competent workforce. Due to cross cultural differences and complexities, public service employees need to embrace the right capabilities in order to effectively deal with international customers. The objective of this study is to examine the relationship between cultural intelligence, emotional intelligence, social intelligence, Islamic work ethics and work performance among public service employees in Malaysia. This study aims to discover whether there is a mediating effect by Islamic work ethics on the relationship between cultural intelligence, emotional intelligence, social intelligence, and work performance. Data were gathered via survey questionnaires from a sample of 174 employees from two government agencies in Malaysia. Data were analysed using the Partial Lease Square (PLS) and Structural Equation Modelling (SEM) software. The results of the study show that the dimension of culture intelligence, namely drive cultural intelligence is the strongest predictor of contextual performance, while dimension of emotion intelligence, namely self-emotion appraisal is the strongest predictor of task performance. Examination of the Islamic work ethics as a mediator found that only the relationship between social intelligence and work performance has a partial mediation effect, even though both cultural intelligence and emotional intelligence significantly influence work performance without the mediator variable. The findings contribute to both practice and theory. Several recommendations are made for future research based on the outcome and limitations of this study.